(untitled) (Research, Society and Development, 2020)
Considering the threat to human life imposed by the pandemic of COVID-19 in Brazil, the present study aims to analyze governmental actions of social distancing of states in the Northeast region to confront COVID-19 in the light of state decrees and relative rates deaths in these states. To this end, a qualitative and quantitative methodology consisting of five stages was developed: (1) implementation of a method of relative effects; (2) analysis of the relative effects regarding the trends of deaths; (3) analysis of the decrees and development of variables; (4) analysis of the polar graph; and, (5) Comparison between the relative death rates of the states and the result presented by the polar graph. The main results assert a delay in restrictive measures by the governments of Ceará and Pernambuco, to the detriment of the measures adopted by most states in the Northeast region of Brazil.